An evolutionary and physiological perspective on cell-substrate adhesion machinery for cell migration - Fierro Morales, Julio C.; Xue, Qian; Roh-Johnson, Minna (Frontiers in Cell and Developmental Biology, 2022)
Cell-substrate adhesion is a critical aspect of many forms of cell migration. Cell adhesion to an extracellular matrix (ECM) generates traction forces necessary for efficient migration. One of the most well-studied structures cells use to adhere to the ECM is focal adhesions which are composed of a multilayered protein complex physically linking the ECM to the intracellular actin cytoskeleton. Much of our understanding of focal adhesions, however, is primarily derived from in-vitro studies in Metazoan systems. Though these studies provide a valuable foundation to the cell-substrate adhesion field, the evolution of cell-substrate adhesion machinery across evolutionary space and the role of focal adhesions in vivo are largely understudied within the field. Furthering investigation in these areas is necessary to bolster our understanding of the role cell-substrate adhesion machinery across Eukaryotes plays during cell migration in physiological contexts such as cancer and pathogenesis. In this review, we review studies of cell-substrate adhesion machinery in organisms evolutionary distant from Metazoa. We also cover the current understanding and ongoing work on how focal adhesions function in single and collective cell migration in an in vivo environment. Finally, we discuss nuances that ought to be considered moving forward and the importance of future investigation in these emerging fields for application in other fields pertinent to adhesion-based processes.